Cloning and characterization of squalene synthase and cycloartenol synthase from Siraitia grosvenorii - Huan Zhao; Qi Tang; Changming Mo; Longhua Bai; Dongping Tu; Xiaojun Ma (Elsevier, 2017)
Mogrosides and steroid saponins are tetracyclic triterpenoids found in Siraitia grosvenorii. Squalene synthase (SQS) and cycloartenol synthase (CAS) are key enzymes in triterpenoid and steroid biosynthesis. In this study, full-length cDNAs of SgSQS and SgCAS were cloned by a rapid amplification of cDNA-ends with polymerase chain reaction (RACE-PCR) approach. The SgSQS cDNA has a 1254 bp open reading frame (ORF) encoding 417 amino acids, and the SgCAS cDNA contains a 2298 bp ORF encoding 765 amino acids. Bioinformatic analysis showed that the deduced SgSQS protein has two transmembrane regions in the C-terminal. Both SgSQS and SgCAS have significantly higher levels in fruits than in other tissues, suggesting that steroids and mogrosides are competitors for the same precursors in fruits. Combined in silico prediction and subcellular localization, experiments in tobacco indicated that SgSQS was probably in the cytoplasm or on the cytoskeleton, and SgCAS was likely located in the nucleus or cytosol. These results will provide a foundation for further study of SgSQS and SgCAS gene functions in S. grosvenorii, and may facilitate improvements in mogroside content in fruit by regulating gene expression.